Measuring the cognitive resources consumed per second for real-time lie-production and recollection: a dual-tasking paradigm - Hu, Chao; Huang, Kun; Hu, Xiaoqing; Liu, Yanshuo; Yuan, Fang; Wang, Qiandong; Fu, Genyue (Frontiers in Psychology, 2015)
This research report presents a novel method of dual-tasking lie-detection. Novel software “Follow Me” was invented for a concurrent eye-hand coordination task during truth-telling/lying. Undergraduate participants were instructed to tell truths on questions about undergraduate school whereas they were instructed to tell lies on interview questions about graduate school, pretending they were graduate students. Throughout the experiment, they operated the “Follow Me” software: moving the mouse pointer to follow a randomly-moving dot on a computer screen. The distance between the mouse pointer tip and the dot center was measured by the software every 50 milliseconds. Frequency of distance fluctuation was analyzed as the index of cognitive effort consumed per second (i.e., “degree of cognitive effort”). The results revealed that the dominant frequency of distance fluctuation was significantly lower during encoding than during retrieving responses; and lower during lying than truth-telling. Thus, dominant frequency of distance fluctuation may be an effective index of cognitive effort. Moreover, both encoding and retrieving bald-faced lies were more cognitively effortful than truth-telling. This novel definition and measurement of degree of cognitive effort may contribute to the research field of deception as well as to many other fields in social cognition.